(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Bronchial asthma (BA) is one of the most common chronic diseases in children, exerting a significant impact not only on the respiratory system but also on the child’s neuropsychological 624ISSN: 2582-4686 SJIF 2021-3.261,SJIF 2022-2.889, 2024-6.875 ResearchBib IF: 9.948 / 2024 VOLUME-5, ISSUE-10 state. This article examines the pathogenetic mechanisms of neurocognitive and psychoemotional disorders in children with BA, including chronic inflammation, hypoxia, therapy effects, and external factors. Based on an analysis of Uzbek and international literature, cognitive deficits such as impairments in memory, attention, and executive functions are highlighted, along with an increased risk of comorbid psychiatric disorders, including ADHD and depression. The clinical outcomes and recommendations for an integrated treatment approach focusing on screening and risk minimization are discussed. The article emphasizes the need for further research to develop personalized strategies for improving patients’ quality of life.